2017
DOI: 10.1016/j.envpol.2016.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of cadmium and uranium in arable soils in Switzerland

Abstract: Mineral phosphorus (P) fertilizers contain contaminants that are potentially hazardous to humans and the environment. Frequent mineral P fertilizer applications can cause heavy metals to accumulate and reach undesirable concentrations in agricultural soils. There is particular concern about Cadmium (Cd) and Uranium (U) accumulation because these metals are toxic and can endanger soil fertility, leach into groundwater, and be taken up by crops. We determined total Cd and U concentrations in more than 400 topsoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(97 citation statements)
references
References 40 publications
4
79
1
10
Order By: Relevance
“…The results of X-ray diffraction revealed kaolinite (Si 4 Al 4 O 10 (OH) 8 ) and illite ((K, H 2 O) 2 (Si) 8 (Al, Mg, Fe) 4 (O) 20 (OH) 4 ) in argillaceous and silty fractions, while goethite (α-FeOOH) and hematite (α-Fe 2 O 3 ) were exclusively found among clay particles. Feldspar ((K, Na, Ca)(Si, Al) 4 O 8 ) and quartz (SiO 2 ) were also identified; feldspar was only found in the sandy fraction, and quartz in all granulometric fractions.…”
Section: Evaluation Of Chromic Luvisol Mineralogical/chemical Composimentioning
confidence: 99%
See 2 more Smart Citations
“…The results of X-ray diffraction revealed kaolinite (Si 4 Al 4 O 10 (OH) 8 ) and illite ((K, H 2 O) 2 (Si) 8 (Al, Mg, Fe) 4 (O) 20 (OH) 4 ) in argillaceous and silty fractions, while goethite (α-FeOOH) and hematite (α-Fe 2 O 3 ) were exclusively found among clay particles. Feldspar ((K, Na, Ca)(Si, Al) 4 O 8 ) and quartz (SiO 2 ) were also identified; feldspar was only found in the sandy fraction, and quartz in all granulometric fractions.…”
Section: Evaluation Of Chromic Luvisol Mineralogical/chemical Composimentioning
confidence: 99%
“…The transfer of cadmium to plants is regulated by the physical and chemical characteristics of soils . Consequently, plants grown in argillaceous soils contaminated with cadmium can assimilate limited (sublethal) amounts of this pollutant, thus maintaining their normal growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, some of these components are undesirable or classified as pollutant that may hamper the beneficial use of fertilizers or the recycling potential of waste streams, in particular regarding the use of phosphogypsum [33,34] In a linear economy and a business as usual scenario, these resources are extracted as long as they can be sold and supplied in response to an apparent market demand and directly contribute to the profits of the phosphate industry. In a Circular Economy, solutions should be sought by joint efforts By implementing enhanced heat recovery system (e.g., Outotec's Heros ® ), the conversion efficiency of sulfur combustion could be increased from close to 58% to 71%, a big step in resource efficiency.…”
Section: Circular Principles and Resource Efficiencymentioning
confidence: 99%
“…At present however, it is unclear how fast and to what degree a reduction of Cd levels in soil can be obtained so as to reduce exposure of Cd below the TWI. Recent inventories in Switzerland (Bigalke et al, 2017) and New Zealand for example showed that inputs of Cd inputs to arable cropping systems have been reduced, but the response of the soil Cd level to such reduced inputs is slow or absent.…”
Section: Introductionmentioning
confidence: 99%